An updated classification of meditation methods using principles of taxonomy and systematics - Nash, Jonathan D.; Newberg, Andrew B. (Frontiers in Psychology, 2023)
This paper revisits the proposal for the classification of meditation methods which we introduced in our initial publication, “Toward a Universal Taxonomy and Definition of Meditation” (Nash, Newberg, and Awasthi, 2013). At that time, we advanced the thesis that meditation methods could be effectively segregated into three orthogonal categories by integrating the taxonomic principle of functional essentialism and the paradigm of Affect and Cognition; and we presented relevant research findings which supported that assertion. This iteration expands upon those theoretical and methodological elements by articulating a more comprehensive Three Tier Classification System which accounts for the full range of meditation methods; and demonstrates how recent neuroscience research continues to validate and support our thesis. This paper also introduces a novel criterion-based protocol for formulating classification systems of meditation methods, and demonstrates how this model can be used to compare and evaluate various other taxonomy proposals that have been published over the past fifteen years.